2011
DOI: 10.1209/0295-5075/95/30008
|View full text |Cite
|
Sign up to set email alerts
|

Quantum correlation and phase transitions in a two-dimensional doubly decorated Ising-Heisenberg model

Abstract: We investigate the pairwise quantum correlation, characterized by quantum entanglement (QE) and quantum discord (QD), of a two-dimensional Ising-Heisenberg model on a planar doubly decorated lattice. At zero temperature, the concurrence (a measurement of pairwise entanglement) and the QD are related to the correlation function qxx and the staggered magnetization δSz, respectively, and both of them indicate the quantum phase transition (QPT) of the system. However, in a finite-temperature phase transition, all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…For instance, quantum discord is found to exhibit long‐range decay as a function of distance in spin chains, where two‐site entanglement is short‐ranged . Furthermore, for some quantum states where the quantum entanglement vanishes thus fails in detecting the quantum phase transitions in the systems, it has been found that the quantum discord survives and plays the role very well . These findings show that quantum discord is a valuable measure of quantum correlations for condensed matter physics.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…For instance, quantum discord is found to exhibit long‐range decay as a function of distance in spin chains, where two‐site entanglement is short‐ranged . Furthermore, for some quantum states where the quantum entanglement vanishes thus fails in detecting the quantum phase transitions in the systems, it has been found that the quantum discord survives and plays the role very well . These findings show that quantum discord is a valuable measure of quantum correlations for condensed matter physics.…”
Section: Introductionmentioning
confidence: 92%
“…For a larger N (which means more sites in the environment block), the sub‐square would share a larger amount of “external” correlations with its environment. Consequently, a smaller amount of “internal” correlations could be reserved in the sub‐square, since the “total” correlations which the 2 × 2 sub‐square can carry is finite . That's why the peak value of the GNλ curves decreases gradually as the increase of N .…”
Section: Gqd In 2d Transverse‐field Ising Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worthwhile to remark, however, that the quantum entanglement and non-locality are distinct albeit closely related features of quantum-mechanical systems [3]. Moreover, it has been evidenced that the quantum entanglement and non-locality are also capable of detecting phase transitions of quantum spin systems [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…It is worthwhile to remark, however, that the quantum entanglement and non-locality are distinct albeit closely related features of quantum-mechanical systems [3]. Moreover, it has been evidenced that the quantum entanglement and non-locality are also capable of detecting phase transitions of quantum spin systems [4][5][6].Quantum effects may have striking macroscopic consequences like for instance presence of quantized plateaux in low-temperature magnetization curves. The magnetization plateaux of quantum spin chains should satisfy Oshikawa-Yamanaka-Affleck rule [7]: p(S u − m u ) = Z, where p is the ground-state period, S u and m u is the total spin and total magnetization of elementary unit and Z is an integer number.…”
mentioning
confidence: 99%